Future energy improved, sustainable and clean options for our planet - Letcher, T. M. (Elsevier, 2008)
Increasing global energy demand requires fact-based evaluations of alternative energy sources. This includes solving questions like how energy is produced, provided, and transported in sustainable ways. Solving future energy demands requires new technologies and knowledge. Decision makers, professionals, and people interested in energy issues in general need to know the relative importance and magnitude of various energy production methods. This book contains contributions by expert scientists and engineers on all of the sources of energy available to us now and in the near future that will enable us to take the energy decisions needed for sustaining development and dealing with climate change. - Each type of available energy is put into perspective and all realistic, future options are examined in detail - Presents theory and background, detailing the magnitude of energy involved - Written by top scientists AND engineers in the various fields.